Pengaruh Kepercayaan, Kemudahan Penggunaan, dan Program Promosi Cashback dalam Penggunaan QRIS terhadap Pengelolaan Keuangan Pribadi Generasi Z di Kabupaten Tasikmalaya - Via Apriani; Agustian, Aldy (Lembaga Pengembangan Kinerja Dosen, 2026)
The rapid growth of QRIS transactions (148.54% in 2025) among Generation Z contrasts with poor personal financial management, especially in poor regions like Tasikmalaya Regency (poverty rate 10.15%). This study aims to analyze the effect of trust, perceived ease of use, and cashback promotion programs on personal financial management of Generation Z in Tasikmalaya Regency. A quantitative causal-associative approach was used with 120 respondents selected by purposive sampling. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression with SPSS. The results show that trust, ease of use, and cashback simultaneously and partially have a positive and significant effect on personal financial management. Ease of use gives the highest contribution (β=0.338), followed by cashback (β=0.230) and trust (β=0.219). The adjusted R-squared is 0.428, meaning 42.8% of the variance in personal financial management is explained by the three variables. This study extends the Technology Acceptance Model (TAM) by linking adoption factors to long-term financial behavior in a low-income rural context and provides implications for financial literacy policy development